A minimally invasive surgery robotic assistant for HALS-SILS techniques - Bauzano-Núñez, Enrique; García-Morales, Isabel; Del Saz-Orozco, Pablo; Fraile-Marinero, Juan Carlos; Muñoz-Martínez, Víctor Fernando (Elsevier, 2013)
This paper is focused in the design and implementation of a robotic surgical motion controller. The proposed control scheme addresses the issues related to the application of a robot assistant in novel surgical scenario, which combines hand assisted laparoscopic surgery (HALS) with the single incision laparoscopic surgery (SILS) techniques. It is designed for collaborating with the surgeon in a natural way, by performing autonomous movements, in order to assist the surgeon during a surgical maneuver. In this way, it is implemented a hierarchical architecture which includes an upper auto-guide velocity planner connected to a low-level force feedback controller. The first one, based on a behavior approach, computes a collision free trajectory of the surgical instrument tip, held by the robot, for reaching a goal location inside of the abdominal cavity. On the other hand, the force feedback controller uses this trajectory for performing the instrument displacement by taking into account the holonomic movement constraints introduced by the fulcrum point. The aim of this controller is positioning the surgical instrument by minimizing the forces exerted over the abdominal wall due to the fulcrum location uncertainty. The overall system has been integrated in the control architecture of the surgical assistant CISOBOT, designed and developed at the University of Malaga. The whole architecture performance has been tested by means of in vitro trials.
Keywords: Cirugía - Aparatos e instrumentos; Robótica; Laparoscopic surgery; Real-time automatic movements; Force feedback control; Surgical robot assistant